Intracortical microstimulation of supplementary eye field impairs ability of monkeys to make serially ordered saccades - Berdyyeva, Tamara K. (American Physiological Society, 2014)
Neurons in the supplementary eye field (SEF) of the macaque monkey exhibit rank selectivity, firing differentially as a function of the phase attained during the performance of a task requiring the execution of saccades to a series of objects in fixed order. The activity of these neurons is commonly thought to represent ordinal position in the service of serial-order performance. However, there is little evidence causally linking neuronal activity in the SEF to sequential behavior. To explore the role of the SEF in serial-order performance, we delivered intracortical microstimulation while monkeys performed a task requiring them to make saccades to three objects in a fixed order on each trial. Microstimulation, considered on average across all SEF sites and all phases of the trial, affected saccadic kinematics. In particular, it prolonged the reaction time, increased the peak velocity, and slightly increased the amplitude of saccades. In addition, it interfered with the monkeys' ability to select the target appropriate to a given phase of the trial. The pattern of the errors was such as would be expected if microstimulation shifted the neural representation of ordinal position toward a later phase of the trial.